2012
DOI: 10.1002/hec.2822
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐inflated Endogenous Count in Censored Model: Effects of Informal Family Care on Formal Health Care

Abstract: If informal family health care is a substitute for formal health care, then there is a scope to reduce formal health care cost by promoting informal family health care. With the use of Korean data for the elderly, this paper estimates the effects of informal family health care on formal health care, where the former is measured by the number of caregivers and the latter is measured by the formal health care expenditure. This task, however, poses a number of difficulties. The first is that the number of the fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, recent simulation research by Terza and colleagues has suggested that IV‐based nonlinear two‐stage residual inclusion (2SRI) estimators—a special case of control function methods (Hausman ; Garrido et al. ; Lee and Kim )—can directly estimate the population average treatment effect (ATE) in models with binary, or otherwise “inherently nonlinear,” dependent variables without relying on these assumptions (Terza, Bradford, and Dismuke ; Terza, Basu, and Rathouz ). As a result, the authors of this research suggest that nonlinear 2SRI should always be employed for analysis of empirical models with inherently nonlinear dependent variables and unmeasured confounding risk (Terza, Basu, and Rathouz ).…”
Section: Treatment Effect Heterogeneity and Choice: Essential Heterogmentioning
confidence: 99%
“…However, recent simulation research by Terza and colleagues has suggested that IV‐based nonlinear two‐stage residual inclusion (2SRI) estimators—a special case of control function methods (Hausman ; Garrido et al. ; Lee and Kim )—can directly estimate the population average treatment effect (ATE) in models with binary, or otherwise “inherently nonlinear,” dependent variables without relying on these assumptions (Terza, Bradford, and Dismuke ; Terza, Basu, and Rathouz ). As a result, the authors of this research suggest that nonlinear 2SRI should always be employed for analysis of empirical models with inherently nonlinear dependent variables and unmeasured confounding risk (Terza, Basu, and Rathouz ).…”
Section: Treatment Effect Heterogeneity and Choice: Essential Heterogmentioning
confidence: 99%
“…Almirall et al . ; Lee and Kim, ); however, this requires some extra modelling effort. Because terms such as v 2 or xv 2 are explicitly accounted for, the error term variance tends to get reduced in the CF approach, which comes at the cost of correctly modelling the function λ ( v 2 ; θ ) or λ ( v 2 , x ; θ ) .…”
Section: Various Approaches To Binary Systemsmentioning
confidence: 99%
“…The substitution effect weakened as the level of recipient disability increased. Lee and Kim () found substitution effects that varied in magnitude by the morbidity of the recipient. Gannon and Davin () used SHARE data for France and Ireland and examined a substitution relationship between informal care and formal home care for those over 50 years old.…”
Section: Introductionmentioning
confidence: 99%